Gambaran Tingkat Pengetahuan Sikap dan Tindakan Masyarakat Terhadap Rumah Sehat di Negeri Mamala Kecamatan Leihitu Kabupaten Maluku Tengah - Rusdin Wally; M Fadly Kaliky (Pusat Riset dan Inovasi Nasional, 2024)
According to the WHO (World Health Organization), housing is a physical structure where people use it for shelter where the environment of the structure is included as well as all facilities and services that are in the hospital, equipment that is useful for physical and spiritual health and good social conditions for families and individuals. A healthy house is one of the health facilities to achieve an optimal degree of health (World Health Organization). To find out the level of knowledge and behavior of the community towards healthy houses in the Land of Tamala, Leihitu District, Central Maluku Regency. The type of research used is descriptive research to obtain an overview of the level of knowledge, attitudes and actions of the community towards healthy houses in the country of Malala, Leihitu District, Central Maluku district. The results of this study show that the knowledge of the people of Mamala has a level of knowledge in the Good Category of 83%, Sufficient as 15%, Lacking as much as 2%, The attitude of the people of Mamala has a good attitude as much as 100%, the actions of the people of Mamala have good actions as much as 53%, Sufficient as much as 47%. Based on the results of the research that has been carried out in Mamala Country, Leihitu District, Central Maluku Regency, it can be concluded that the public's knowledge about healthy houses is in the good category with a presentation of 83%, the attitude of the respondents is in the good category with a percentage of 100%, and the action is in the good category with a percentage of 53%.